Residual stress analysis in torsion of elliptical sectioned bar of non-linear work-hardening materials - Lal R.K.; Choubey V.K.; Dwivedi J.P.; Kumar S.; Shah S.K. (My University, 2025)
In this paper, a complete theory and reliable mathematical models for Triangular cross-sectioned bars of linear work-hardening materials have been established to predict residual stress under torsional loading. © 2017 Elsevier Ltd.